2023
DOI: 10.1039/d2re00288d
|View full text |Cite
|
Sign up to set email alerts
|

Anionic synthesis and end-functionalization of polymyrcene in a flow microreactor system

Abstract: In the search for flexible and sustainable methods for the synthesis of macromolecular scaffolds, microflow systems exhibit unrivalled qualities, as exemplified by the fine control on mass and thermal transfers....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The development of more rigorous and safe polymerization reactions of bio-based monomers is a major topic in the present era. Pérez et al 209 from Normandie University in France reported the excellent performance of microreactors in finding flexible and sustainable methods for the synthesis of macromolecular scaffolds. It is found that the anionic polymerization of myrcene can be fine-tuned in a microfluidic reactor to produce low molar mass polymyrcene (PMYR).…”
Section: Synthesis Of Micro/nanomaterials By Microreactorsmentioning
confidence: 99%
“…The development of more rigorous and safe polymerization reactions of bio-based monomers is a major topic in the present era. Pérez et al 209 from Normandie University in France reported the excellent performance of microreactors in finding flexible and sustainable methods for the synthesis of macromolecular scaffolds. It is found that the anionic polymerization of myrcene can be fine-tuned in a microfluidic reactor to produce low molar mass polymyrcene (PMYR).…”
Section: Synthesis Of Micro/nanomaterials By Microreactorsmentioning
confidence: 99%
“…toxicity of the effluent could be mitigated by including an additional downstream process, directly injecting CO 2 gas to form the innocuous benzoic acid. 24,30,33 Attention shall also be paid to the accumulation of flammable volatiles at the reactor outlet.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…[14][15][16][17][18] Fluidic systems offer the possibility to handle and treat large volumes of hazardous compounds with reduced exposition for the operator. 19 Following the pioneer work of Yoshida, [20][21][22][23][24] highly reactive organometallic species (mostly organolithium compounds [25][26][27][28][29][30] and then Grignard reagents [31][32][33] ) were shown to be easily controlled in flow microreactors. [34][35][36] In addition, the fine control brought by miniaturised flow reactors on various parameters (reaction time, temperature) and the spatial resolution of the reaction allowed to obtain the high selectivities required for the effective detoxification of chemical warfare agents.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous flow reactors are emerging as a new technology in the synthesis of well-defined polymers owing to their advantages over batch reactors such as high mixing efficiency, fast mass and heat transfer rates, reduced energy input, and precise control of operation parameters. A number of end-functionalized polymers and block copolymers have been synthesized from living or controlled polymerization in a continuous way by setting up specific configuration of the flow reactors and the feed inlets. These processes are highly automated, enabling the digitalization of polymer production with various functionalities and topologies. Nevertheless, the study of ROP of D 4 in flow reactors is scarce.…”
Section: Introductionmentioning
confidence: 99%